The Politics of Secularism in International Relations - Hurd, Elizabeth Shakman, 1970- (Book collections on Project MUSE., 2008)
Conflicts involving religion have returned to the forefront of international relations. And yet political scientists and policymakers have continued to assume that religion has long been privatized in the West. This secularist assumption ignores the contestation surrounding the category of the "secular" in international politics. The Politics of Secularism in International Relations shows why this thinking is flawed, and provides a powerful alternative.